Abonamiento con dosis de ceniza de madera y distanciamientos de siembra y su influencia en las características agronómicas y rendimiento de Brassica oleracea L. var. Itálica "brócoli", en Zungarococha-Loreto. 2021 - Sandoval Camiñas, Pedro Eglinton (2022)
The research was carried out in the Teaching and Research Workshop on Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located in the "Zungarococha" farm, south of the city of Iquitos, Km. 4 of the road to Llanchama . The type of study was experimental, explanatory, cross-sectional with two independent variables (Wood ash dose and planting spacing) and eight dependent variables (Plant height, Plant diameter, number of leaves/plants, root length). , diameter of the pellet, total weight of the plant, weight of the pellet and weight of pellets/ha). The objective was to determine if fertilization with doses of wood ash and planting distances influence the agronomic characteristics and yield of Brassica oleracea L. var. Itálica “broccoli”, in Zungarococha-Loreto. 2021. The Statistical Design used was the Completely Randomized Block Design, with eight treatments and four repetitions. Each experimental unit consisted of 2 rows, 4 plants/row and the sampling unit consisted of four plants/experimental unit where the following conclusions were reached: The highest dose of wood ash and the greatest planting distance in Treatment T8 (3 t of wood ash/ha; 0.60 m x 0.50 m) presented the highest plant height, with 67 cm; Treatment T1 (0 t of wood ash/ha; 0.50 m x 0.50 m), presented the greatest root length, with 20 cm; Treatment T6 (2 t of wood ash/ha; 0.60 m x 0.50 m), presented the greatest number of leaves, with 16 units, greater pellet diameter, with 15 cm, greater total plant weight, with 485 g, greater pellet weight, with 66 g; Treatment T5 (2 t of wood ash/ha; 0.50 m x 0.50 m), presented the largest plant diameter, with 42 cm, and the highest weight of pellets/ha with 1440 Kg; Treatment T5 (2 t of wood ash/ha; 0.50 m x 0.50 m), had the best Benefit-Cost ratio of the crop with S/.9,910.00.